The Social reproduction of the medical profession the case of the University of the Philippines-Philippine General Hospital Medical Center - Sana, Erlyn A. (1999)
Among the health professions, medicine enjoys the most prestigious and powerful position in the medical and other health-related institutions. It is associated with a distinct set of knowledge and skills that make both the health and non-health professions depend on them a great deal. Similarly, the institutions that reproduce the medical professions are also regarded highly by modern societies. This study looked at the various social structures in the form of rules and resources pertinent to medical clerkship and internship in a medical center in the process of socially reproducing the medical professions. The study used the case of the medical clerks and interns of the University of the Philippines-Philippine General Hospital Medical Center. Data were collected using a combination of direct observation, survey, key informant interviews and secondary data analysis. Four blocks of interns and one group of medical clerks were observed for 54 days as they rotated in the four core clinical departments of the medical center namely, the Departments of Medicine, Obstetrics-Gynecology, Surgery and Pediatrics. The study shows that the very structures of medical education at the UP-PGH Medical Center especially the clerkship and internship training program in the form of the official, operational and hidden curricula, together with the highly specialized physical environment where the training takes place, all collectively and socially reproduce the medical professions. The medical center imposes rigid and continuous recruitment policies to weed out trainees who cannot hurdle the training. Initially only those who were able to demonstrate outstanding performance in pre-medical academic pursuits get admitted to UP-PGH. This holds true even to the case of the post-graduate interns: graduates of other medical schools. At the UP College of Medicine, the same rigid selection procedures in the form of written and oral examination are given. As these medical students rotate in the various clinical areas during their clerkship and internship, they are still being continuously screened and their progress monitored to ensure that only the most able, determined and competent would remain. It is also integral in the structures of the training for the medical students to depend on their batch mates. As they find this training more and more difficult, the more that they realize the need to work as a group such that by the time they have completed their internship, these medical students have already developed into a strong, homogenous and functional learning group. Findings show that the combined structures of imposing strict recruitment procedures and developing a strong sense of unity among the medical students slowly but surely equip them with a very powerful resource: mastery of medical knowledge. Data show that all the structures of the training are directed to the students' acquisition and mastery of medical knowledge, development of clinical skills and professional attitudes. And since this medical field is an essential concern of society, e.g. health and life itself, it becomes imperative that society accords these individuals with the highest occupational prestige. In the final analysis, the whole process of medical education proves that it is socially reproducing the medical clerks and interns as a uniform elite group. They are called so because of the closed recruitment procedures that they are subjected into their strong sense of belonging to the group. The data also show that they develop into a uniform type of elite group because of their strong knowledge base: possession and mastery of medical knowledge. During the entire process of social reproduction of the medical professions at UP-PGH, various traditions were identified as self-perpetuating. These include the traditions of hierarchy and inequality between the senior and junior medical personnel, between the medical and non medical personnel, between the paying and the charity patients and even between gender orientations. Strong and evolving traditions of coping with a demanding clinical training were also described such as gulangan and sunugan. A serendipitous finding obtained from the data relates to the doctor-patient-bantay relationship. It describes the course of patients in the hospital and the ensuing partnership that develops among the three key players. It was noted that the "bantays" are peculiar to this medical training because nowhere else in the world can this non-medical person be found in the clinics, much less allowing them to perform some clinical errands for the patients. These traditions show that medical clerks and interns at UP-PGH are given a multi-faceted training and one that reflects some basic Filipino traits notably that of depending on the family in sickness or in health.